Developmental Competence of Early Stage Porcine Embryos Cultured in Medium with Different Energy Substrate in vitro - Kazuhiro Kikuchi; Mokhamad Fahrudin; Ni Wayan Kurniani Karja (Indonesian Journal of Biotechnology, 2006)
To elucidate the effect of energy requirement during the early embryonic development on their developmental ability to develop to blastocyst stage, in vitro fertilized (IVF) porcine one-cell embryos were cultured in modified North Carolina State University (NCSU)-37 supplemented with different energy substrate. Result indicated that the cleavage rate of embryos in Pyr-Lac and Gluc-Pyr-Lact groups was significantly higher than in those in Gluc group and Gluc-Rib group (P < 0.05). At Day 6 of culture, the highest proportion of embryos develop to the blastocyst stage was obtained in the presence of pyruvate-lactate only. In the medium with glucose, the addition of pyruvate-lactate or ribose slightly increased the proportion of embryos develop to the blastocyst stage, however the value were not significantly different form those obtained in the presence of glucose only. The mean cell number in blastocysts derived from Pyr-Lac and Gluc-Pyr-Lact groups were significantly higher than those in the Gluc group (P < 0.05). These results indicated that the presence of glucose only, as energy substrate, during the first 2 days of in vitro culture (IVC) caused a decrease in development of in vitro produced (IVP) porcine embryos to the blastocyst stage and mean cell number in blastocysts.